The Outsourcing Paradox: A Critical Analysis of Efficiency and Efficacy in Nigerian Federal Tertiary Educational Institutions - Cheri, Lawan; Kaku, Mohammed; Goni , Umar Mohammed; Aliyu, Aliyu Sabo (Kashere Journal of Politics and International Relations, 2025)
The study examines the effects of the Nigerian federal government’s outsourcing policies on Tertiary educational institutions (TEIs) in Nigeria, focusing on their impact on organizational efficiency, student academic performance, and the broader socio-economic landscape. Drawing on data from 22 in-depth interviews and three focus group discussions across three federal institutions in Yobe state, the research employed purposive, quota, and snowball sampling. Thematic analysis revealed that while the policy has led to perceived benefits such as cost savings and a reduced supervisory burden for institutions, these gains are significantly undermined by systemic implementation failures. Findings indicate a decline in the quality of non-core services like cleaning and security, which has created an unconducive academic environment and contributed to a rise in theft across the affected TEIs. Furthermore, the policy has been found to have severe socio-economic consequences, including staff retrenchment and the exploitation of workers through sub-minimum wage payments. The study concludes that the policy’s failures are not inherent to the concept of outsourcing but are a direct result of poor governance, lack of monitoring, and inadequate oversight. It calls for a fundamental re-evaluation of the policy’s implementation, urging for a new approach that prioritizes ethical labor practices, transparent accountability, and robust governance to ensure that the policies genuinely serve the best interests of both the institutions and the public they serve.